EFFECT OF TEACHING STYLES AND MOTOR ABILITY ON RESULTS LEARNING SEPAK TAKRAW BASIC TECHNIQUES - Zulkifli, Zulkifli; Asmawi, Moch.; Hanif, Ahcmad Sofyan (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2018)
The purpose of this study to find the effectiveness of teaching styles to the basic learning techniques sepaktaraw seen from motor ability. The method used is experiment with 2x3 factorial treatment design. The population used as the target population is the students of Physical Education Health and Recreation Universitas Islam Riau Force 2015/2016 totaling 129 consisting of 115 sons and 14 daughters. Sampling was done by purposive sampling technique. Hypothesis test 1) The difference between the reciprocal teaching style group (A1) and the teaching style group Exercise (A2) worth = 0.035 <0.05, mean H0 is rejected. 2) The difference between the reciprocal teaching style group (A1) and the inclusion teaching style group (A3) = 0.0005 <0.05, H0 is rejected. 3) The difference between the teaching exercise style group (A2) and the inclusion teaching group (A3) = 0,045 <0.05, H0 is rejected. 4) Influence Interaction (Interaction Effect) Fo (AB) worth = 0,000 <0,05 or H0 is rejected. 5) Differences in learning outcomes of basic techniques sepak takraw between reciprocal teaching style that has a high ability motor with practice teaching style that has a low ability motor (A1B1 x A2B1) worth = 0.00 <0.05 or H0 rejected. 6) The difference in learning outcomes of basic techniques sepak takraw between reciprocal forces that have high ability motor with inclusion force that has high ability motor (A1B1 x A3B1) worth = 0,000 <0,05 or H0 is rejected. 7) Differences in learning outcomes of basic techniques sepak takraw between training styles that have high ability motor with an inclusion force that has a high ability motor (A2B1 x A3B1) worth = 0.000 <0.05 or H0 rejected. 8) Differences in learning outcomes of basic techniques sepak takraw between reciprocal teaching styles that have low ability motor with exercise style with low ability motor (A1B2 x A2B2) worth = = 0.485> 0.05 or H0 accepted. 9) Differences in learning outcomes of basic techniques sepak takraw between reciprocal teaching styles that have low ability motor with inclusive teaching style that has low ability motor (A1B2 x A3B2) worth = = 0.025> 0.05 or H0 rejected. 10) Differences in learning outcomes of basic techniques sepak takraw between teaching style exercises that have low ability motor with inclusive teaching style that has low ability motor (A2B2 x A3B2) worth = = 0.029> 0.05 or H0 is rejected.   Keywords: Learning result of basic technique sepak takraw, teaching style and motor ability